2019
DOI: 10.1016/j.cub.2019.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Theta Networks in the Human Medial Temporal Lobe Support Episodic Memory

Abstract: Highlights d We assessed intra-MTL connectivity during a memory task in 131 epilepsy patients d Successful encoding and retrieval were correlated with elevated theta connectivity d Left entorhinal cortex emerged as a hub of intra-MTL connectivity d We found broad increases in high-frequency power but decreases in theta power

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
120
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(144 citation statements)
references
References 65 publications
(122 reference statements)
23
120
1
Order By: Relevance
“…Kucewicz and colleagues demonstrated that memory related broadband gamma activity centroids were in the range of 30-100Hz (Kucewicz MT, et al, 2017). Two recent studies on human memory network analysis with a pooled cohort of patients similar to that included in this study, have shown that successful memory encoding is associated with asynchronous organization of the memory network in gamma activity less than 100Hz and synchronous theta activity, with widespread high gamma activity considered to be the hallmark of memory encoding (Solomon EA, et al, 2017;Solomon EA, et al, 2019). In this project, we were interested in investigating the intrinsic BOLD correlations of a high frequency network already known to play a major role in human memory, all toward determining if such networks possess distinctive whole-brain organization properties.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Kucewicz and colleagues demonstrated that memory related broadband gamma activity centroids were in the range of 30-100Hz (Kucewicz MT, et al, 2017). Two recent studies on human memory network analysis with a pooled cohort of patients similar to that included in this study, have shown that successful memory encoding is associated with asynchronous organization of the memory network in gamma activity less than 100Hz and synchronous theta activity, with widespread high gamma activity considered to be the hallmark of memory encoding (Solomon EA, et al, 2017;Solomon EA, et al, 2019). In this project, we were interested in investigating the intrinsic BOLD correlations of a high frequency network already known to play a major role in human memory, all toward determining if such networks possess distinctive whole-brain organization properties.…”
Section: Introductionmentioning
confidence: 61%
“…Successful episodic verbal memory encoding, termed the 'Subsequent Memory Effect' (SME) is associated with high-frequency gamma activity (ranging from 30-100Hz) captured using power spectral and synchronization studies during invasive electroencephalography (IEEG) in association with neuronal firing Kucewicz MT et al, 2017;Lega BC et al, 2012;Long NM et al, 2014;Sederberg PB et al, 2006;Serruya MD et al, 2014;Solomon EA et al, 2017;Solomon EA et al, 2019). Despite these well-established linkages, relatively little is known about the whole-brain organization of HFA regions and the degree to which these regions possess either distinct network features relative to other brain areas, or rely on abnormal organizational properties due to epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…The first goal of our study was to characterize the intrinsic spectro-temporal organization of the DMN. Analysis of the spectral properties of the human DMN has been necessarily constrained by limited placement of iEEG electrodes, consequently previous work has mainly focused on activation and deactivation in isolated nodes of the network (Ossandon T et al 2011;Lopour BA et al 2013;Daitch AL and J Parvizi 2018;Solomon EA et al 2019). It is currently impossible to acquire iEEG data across the entire human brain with resolutions matching those of fMRI.…”
Section: Intrinsic Spectro-temporal Network Organization Of the Dmnmentioning
confidence: 99%
“…To address this, we first examined frequency-specific iEEG phase synchronization during a verbal episodic memory task in which participants had to subsequently recall a list of visuallypresented words (Solomon EA et al 2019). Our analysis procedures were identical to those used in the case of resting-state iEEG data.…”
Section: Dmn Phase Synchronization and Spectral Integrity Is Preservementioning
confidence: 99%
See 1 more Smart Citation